Prevalence and Predictors of Radiographically Apparent Upper Urinary Tract Urolithiasis in Eight Dog Breeds Predisposed to Calcium Oxalate Urolithiasis and Mixed Breed Dogs - Alexis M. Hoelmer; Jody P. Lulich; Aaron K. Rendahl; Eva Furrow (Veterinary Sciences, 2022)
Data on upper urinary tract (UUT) uroliths in dogs are important to understanding their etiology. The aim of this retrospective case-control study was to determine the prevalence and identify predictors of radiographically apparent UUT uroliths in dog breeds at increased risk for calcium oxalate uroliths (CaOx risk breeds) and mixed breed dogs. Radiologist reports of three-view abdominal radiographs were reviewed from 251 purebred dogs of 8 CaOx risk breeds and 68 mixed breed dogs. UUT uroliths were more common in CaOx risk breeds than mixed breed dogs (23% versus 6%, respectively; OR = 4.8, 95% confidence interval [CI] 1.7–18.9, p < 0.001). UUT uroliths were more common in dogs with lower urinary tract (LUT) uroliths (predominantly calcium-containing) than those without (41% versus 5%, respectively; OR = 13.6, 95% CI 6.3–33.1, p < 0.001), and LUT uroliths predicted the presence of UUT uroliths in the multivariable regression (OR = 6.5, 95% CI 2.8–16.7, p < 0.001). Increasing age (p < 0.001) and lower body weight (p = 0.0016) were also predictors of UUT urolith presence in the multivariable regression. The high prevalence of UUT uroliths in dogs with LUT uroliths supports a shared mechanism for their formation.